ابتلا کا قرآنی فلسفہ اور عصر حاضر کے مفکرین کا بیانیہ: The Qur’anic Philosophy of Trial and the Narrative of Contemporary Muslim Thinkers - Dr. Shazia; Hafiza Iqra Nawaz (Al-Amīr Research Journal for Islamic Studies, 2025)
In Islamic teachings, human life is described as a continuous test. According to the Qur’an and Sunnah, this world is a place of trial (Dar al-Ibtalā), where man is tested through various conditions such as joy and sorrow, wealth and poverty, ease and hardship, health and sickness, peace and fear.Classical Muslim scholars such as al-Ghazali, Ibn Taymiyyah, Ibn al-Qayyim, and Shah Waliullah interpreted trials as a source of spiritual training and nearness to Allah. Contemporary thinkers such as Allama Iqbal, Maulana Maududi., Wahiduddin Khan,Yusuf al-Qaradawi, Javed Ahmad Ghamidi, and Tariq Ramadan have analyzed the Qur’anic philosophy of trials in the light of modern challenges.This article highlights the Qur’anic philosophy of trials, elaborates on classical and modern scholarly perspectives, and provides an in-depth analysis for understanding the role of trials in shaping the moral, spiritual, and intellectual development of Muslims in the contemporary world. Keywords: Qur’an, Trial, Patience, Gratitude, Islamic Thinkers, Contemporary Challenges.